A case of mucopolysaccharidoses type I with heart involvement during infancy - Demirsoy, Sadık; Gücüyener, Kıvılcım; Olguntürk, Rana; Tunaoğlu, Sedef; Oğuz, Deniz (The Turkish Journal of Pediatrics, 1990)
We report a case of mucopolysaccharidoses I with severe cardiac involvement, which was diagnosed on the basis of clinical and laboratory findings even though, symptoms begin to occur in mucopolysaccharidoses after the first year of life. In our case cardiac failure occurred in the third month of life, which resulted in the patient’s death after one month.